Factors Associated with the Incidence of Stunting in 18 - 24 Months Old Children in Malaka Village, Sumedang District, West Java, Indonesia - Nia Reviani; Joshua Harmani; Reza Fitriani; Faulina Panjaitan; Eunike Malau; Kenny Timisela (Majalah Kedokteran UKI, 2019)
Abstract Stunting has been one of major concerns for the Indonesian government. In 2013, Indonesia reached the number of 37.2% for national stunting incidence, constantly increasing from year 2010 (35.6%) and 2007 (36.8%) according to Indonesian Basic Health Research (Riset Kesehatan Dasar). The National Nutrition Status Monitoring (Pemantauan Status Gizi) in 2017 recorded that 17.8% children of Indonesia weremalnourished and 12.1% of them were stunted. Whereas data from the Ministry of Health of the Republic of Indonesia in 2017 showed that the prevalence of underfives nationally with stunting was 29.6%. At provincial level, West Java ranked 26th with 35.3% as the number of stunting incidence. Sumedang District is one of 100 districts assigned as the main focus for stunting intervention program. In addition, Malaka Village in Sumedang District is one of 1,000 villages in Indonesia designed to be intervened as it held a high incident of children suffering from stunting. This study was aimed to find the association between birth length, birth weight, family economic status, exclusive breastfeeding, mother’s knowledge with the incidence of stunting in children aged 24-48 months old. The total sample of the study was 62 children, determined through accidental (convenience) sampling. Malaka Village had a prevalence of stunted children at a percentage of 27.4%. From univariate analysis with Spearman’s Rho correlation test, birth length and exclusive breastfeeding showed significant associations with stunting while other factors failed to demonstrate such associations. Keywords: malnutrition, birth length, birth weight, exclusive breastfeeding Abstrak Stunting merupakan salah satu permasalahan utama bagi pemerintahan Indonesia. Pada tahun 2013, insiden stunting secara nasional di Indonesia mencapai 37.2%. Angka ini meningkat terus-menerus sejak tahun 2010 (35.6%) dan 2007 (36.8%) berdasarkan data dari Riskesdas. Pemantauan Status Gizi tahun 2017 mencatat bahwa 17.8% anak-anak Indonesia mengalami malnutrisi dan 12.1% di antaranya juga mengalami stunting. Data dari Menteri Kesehatan Republik Indonesia pada tahun 2017 menunjukkan bahwa prevalensi balita stunting sebesar 29.6%. Pada tingkat provinsi, Jawa Barat berada pada peringkat 26 dengan insiden stunting sebesar 35.3%. Kabupaten Sumedang merupakan salah satu dari 100 kabupaten yang ditetapkan sebagai focus intervensi stunting. Desa Malaka pada KabupatenSumedang juga merupakan salah satu dari 1,000 desa di Indonesia yang akan dilakukan intervensi sunting karena angka kejadian stunting yang cukup tinggi. Penelitian ini bertujuan untuk mencari hubungan antara panjang badan lahir, berat badan lahir, status ekonomi keluarga, ASI eksklusif, pengetahuan gizi ibu terhadap kejadian stunting pada anakusia 2448 bulan. Total sampel dari penelitian ini sejumlah 62, yang ditentukan dengan accidental (convenience) sampling. Prevalensi anak stunting di Desa Malaka ditemukan sebesar 27.4%. Dengan analisis univariat menggunakan uji korelasi Spearman Rho, didapatkan bahwa panjang badan lahir dan ASI eksklusif memiliki hubungan yang signifikan terhadap kejadian stunting, sedangkan faktor lainnya tidak menunjukkan hubungan yang signifikan. Kata kunci: malnutrisi, panjang badan lahir, berat badan lahir, ASI eksklusif